The new aesthetic in contemporary world painting (Al-Academy, 2023)
The research tagged: the new aesthetic in contemporary world painting. The research contained five chapters. The first chapter dealt with the research problem and its importance. It dealt with the concept of the new aesthetic as a concept concerned with the topics of the mind, i.e. the most comprehensive and diverse topics. The New Aesthetic is an aesthetic and stylistic structure whose taste, aesthetic, artistic and emotional contribute to its structure with awareness of the context. The aim of the research is to identify the new aesthetic in contemporary world painting. As for the objective limits of the research, the researcher was interested in studying the new aesthetic, especially in abstract expressionism, pop art, opera, and conceptual art, for the period (1948-1997) in America. The chapter also included keywords. The second chapter dealt with the concept of beauty and aesthetics. The third chapter dealt with aesthetics and awareness of the cultural and social context in modern painting. The fourth chapter dealt with the new aesthetic and its applications in contemporary formation. In the fifth chapter, the researcher reached a set of results, including:1-The new aesthetic found in expressionism a space that was able to reproduce the above, in a psychological space, after which the artist turned to search for his own personal visions and ideas, just as surrealism was the influential reference with its ancient symbols and myths, which gave the artists of abstract expressionism an opportunity to express meanings latent by the most obvious means.2- Visual data, including multimedia in pop art, formed new aesthetic approaches, and it is part of the exchange of ideas and its philosophy in time.Then, the researcher reached a set of conclusions, and then a list of sources, references, and a summary of the research in English.